ACTR-45. PHASE 0/2 STUDY OF RIBOCICLIB IN PATIENTS WITH RECURRENT GLIOBLASTOMA. (5th November 2018) - Tien, An-Chi; Bao, Xun; Derogatis, Alanna; Kim, Seongho; Mehta, Shwetal; Li, Jing; Sanai, Nader
Abstract: BACKGROUND: CDK4/6-dependent cell-cycle regulation is disrupted in 78% of glioblastoma patients. We conducted a Phase 0/2 clinical trial (NCT02933736) of ribociclib, a selective CDK4/6-inhibitor, to examine the plasma and tumor pharmacokinetics (PK) and pharmacodynamics (PD) of recurrent glioblastoma. METHODS: Eligible patients with intact RB expression and CDKN2A deletion or CDK4/6 amplification were enrolled into the Phase 0 component to receive ribociclib (900mg daily) for 5 days prior to tumor resection. Plasma, tumor, and CSF samples were collected to determine drug concentrations using validated LC-MS/MS methods. PD effects, including RB and FoxM1 phosphorylation, were compared to archival tissue. Patients with favorable PK and PD outcomes were transitioned into the Phase 2 component. RESULTS: Twelve patients were enrolled into three presurgical time-escalation groups (2-hours, 8-hours, 24-hours). Ribociclib penetrated both enhancing and non-enhancing regions of the tumor. In non-enhancing tissue, median unbound brain-to-plasma ratio was 1.78 and median ribociclib concentration was 0.54 nmol/mL, exceeding the in vitro IC50 for CDK4/6 (0.04 nmol/mL). Suppression of G1-to-S phase was inferred by a decrease in RB phosphorylation (p<0.01) and cell proliferation (p<0.05). Six patients (50%) were graduated to the Phase 2 component and demonstrated a median progression-free survival of 9.7 weeks (95% CI, 6.3 to 40 weeks). Tissue samples from re-resection following Phase 2 study identified mTOR pathway upregulation as a candidate resistance mechanism to ribociclib monotherapy. CONCLUSION: Ribociclib penetrates the tumor-brain barrier, achieving pharmacologically-active concentrations in human glioblastoma and suppressing tumor proliferation. Phase 2 study results suggest ribociclib is ineffective as a monotherapy, but analysis of ribociclib-resistant tumors identified the addition of an mTOR inhibitor as a dual-drug strategy for recurrent glioblastoma.